Review of EPA's Environmental Monitoring and Assessment Program : overall evaluation - National Research Council (U.S.). Committee to Review the EPA's Environmental Monitoring and Assessment Program (Washington, D.C. : [Distributed by the National Academy Press], 1995)
Reviewing EPA's Environmental Monitoring and Assessment Program (EMAP), this volume retains its belief that EMAP's goals are laudable. Achieving the goals of this ambitious program requires that EMAP successfully meet the difficult scientific, practical, and management challenges. It questions whether and how well all these goals can be achieved.
Select a Set of Indicators -- Revise Sampling Design -- Information-Management System -- Publish Study Results -- Delay Full Implementation Until Results of Demonstration Projects are Evaluated -- GREAT LAKES -- Conclusions -- SURFACE WATERS -- Background and Objectives -- Assessment End Points -- Indicators -- Sampling Design -- Lake Pilot Project -- Streams -- Intra-Agency Cooperation -- Oversight And Coordination Among EMAP Resource Groups -- EMAP-Center Organization -- References -- Appendix A September 20, 1994 letter from Dr. Edward Martinko, Director, EMAP -- SELECTED EMAP CHANGES OCCURRING FROM 1992 TO THE PRESENT -- Indicator Development -- Sampling Design -- Detection of Trends -- Landscapes -- Analysis of EMAP Data, Particularly Estuaries, and Publication of Results -- Information Management -- Assessment, Integration and Coordination -- Cause-and-Effect Relationships Need More Focused Planning -- Program Management -- Involvement of the Scientific Community and Peer Review -- Inter-Agency and Intra-Agency Cooperation -- Appendix B May 4, 1994 letter from Gary J. Foley, EPA Acting Assistant Administrator for Research a ... -- Appendix C EMAP Documents Reviewed by NRC Committee -- Appendix D Biographical Sketches of Committee Members.
Includes bibliographical references (pages 99-104).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: United States. -- Environmental Protection Agency. -- Environmental Monitoring and Assessment Program; United States. -- Environmental Protection Agency. -- Environmental Monitoring and Assessment Program; Environmental monitoring -- United States; Environnement -- Surveillance -- États-Unis.; SCIENCE -- Environmental Science (see also Chemistry -- Environmental); POLITICAL SCIENCE -- Public Policy -- Environmental Policy; Environmental monitoring; United States